2020
DOI: 10.1590/0037-8682-0016-2020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of intraperitoneal etanercept administration on oxidative stress and inflammation indicators in the kidney and blood of experimental sepsis-induced rats

Abstract: Introduction: Sepsis is an important cause of mortality and morbidity, and inflammatory response and oxidative stress play major roles underlying its pathophysiology. Here, we evaluated the effect of intraperitoneal etanercept administration on oxidative stress and inflammation indicators in the kidney and blood of experimental sepsis-induced rats. Methods: Twenty-eight adult Sprague Dawley rats were classified into Control (Group 1), Sepsis (Group 2), Sepsis+Cefazolin (Group 3), and Sepsis+Cefazolin+Etanercep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Sepsis brings about a large proportion of mortality and morbidity all over the globe, with inflammation and oxidative stress playing crucial roles (Aydin et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis brings about a large proportion of mortality and morbidity all over the globe, with inflammation and oxidative stress playing crucial roles (Aydin et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…An imbalance of the oxidant-antioxidant system leaning towards the dominance of oxidants during inflammation will lead to oxidative stress. Accumulating evidence has revealed that oxidative stress is as important as inflammation with respect to the pathophysiology of sepsis, as numerous drug candidates exert their protective effects on septic AKI via the suppression of inflammation as well as oxidative stress, and these drugs include etanercept, honokiol and glycyrrhizic acid (23)(24)(25). In the present study, the results also illustrated that PINO could significantly attenuate oxidative stress by reducing MDA production and increasing the level of GSH in LPS-challenged HK-2 cells, further affirming the protective role of PINO in septic AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, great effort was made to develop potent inhibitors targeting cytokines like TNF‐α, IL‐1, and IL‐6 or their corresponding receptors leading to the generation of highly specific and effective clinically validated compounds like etanercept, anakinra, and tocilizumab [134]. Based on their efficacy in preclinical sepsis models, great hope has been placed in these small molecular inhibitors and antagonistic monoclonal antibodies [135–138]. However, none of them did add significant benefit for the treatment of sepsis or septic shock in clinical trials.…”
Section: Summary and Perspectivesmentioning
confidence: 99%